Upaya Komisi Pemilihan Umum Provinsi Sumatera Selatan dalam Meningkatkan Partisipasi Pemilih pada Pilkada Serentak 2018 dan Pemilu Serentak 2019 - Andi Chandra; Erik Darmawan; Yesi Yesi (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2018)
This study explains the efforts of the South Sumatra Provincial Election Commission in increasing the political participation of the people of South Sumatra in the 2018 Simultaneous Local Election and 2019 Concurrent Elections. Democracy is determined by the voice of the people, and is closely related to legitimacy